SHANK2 protein contributes to sevoflurane-induced developmental neurotoxicity and cognitive dysfunction in C57BL/6 male mice - Song, Shaoyong; Zhao, Weiming; Ji, Yumeng; Huang, Qinghong; Li, Yixuan; Chen, Shiwen; Yang, Jianping; Jin, Xin (ANESTHESIOLOGY AND PERIOPERATIVE SCIENCE, 2023)
Purpose Repeated exposures to sevoflurane could induce epigenetic modifications in specific brain regions and cognitive impairments in the immature mice. Conflicting findings make neurobehavioral manifestations intricate and potential mechanisms elusive. Influence of neonatal anesthesia with sevoflurane on the expression of synaptic scaffold proteins and neuronal activity remains to be determined. Methods C57BL/6 male and female mice in breeding ages were used to produce next generation. The offspring male mice were randomly scheduled to receive 3.0% sevoflurane plus 60% oxygen for 2 h daily at postnatal day (P) 6–8. Three-chambered social paradigm was used to test social affiliation and social memory. Morris water maze was used to test learning and memory. Whole genome bisulfite sequencing (WGBS), differentially methylated regions (DMRs) and KEGG enrichment analysis were performed to screen target gene in sequence context of CG. RT-PCR and immunoblotting analysis were used to assess expression of the Shank gene family, as well as DNA methylases. Results The male mice undergoing sevoflurane anesthesia at P6-8 showed diminished preference for novel conspecific and prolonged escape latency and decreased platform-crossing times. The sevoflurane-exposed mice showed reduced mRNA and protein levels of the Shank2 gene. KEGG analysis disclosed the role of DNA hypermethylation of Shank2 gene in the pathway of glutamatergic synapse. In addition, sevoflurane anesthesia reduced mRNA and protein levels of the TET3 enzyme. Conclusion Repeated exposures to sevoflurane in neonatal period could impair social recognition memory and spatial reference memory in the male mice. Reduction of hippocampal SHANK2 protein could contribute to sevoflurane-induced neurotoxicity in the immature mice. Reduction of the TET3 enzyme should be responsible for DNA hypermethylation-related silencing of the Shank2 gene. Graphical Abstract